VP205 Implementing Electronic Records In Ambulances. (2017) - Porter, Alison; Black, Sarah; Dale, Jeremy; Fitzpatrick, David; Harris-Mayes, Robert; Lawrenson, Robin; Lyons, Ronan; Mason, Suzanne; Morrison, Zoe; Mountain, Pauline; Potts, Henry; Siriwardena, Niro; et al.
Abstract : INTRODUCTION: Increasingly, ambulance services offer alternatives to transfer to the emergency department (ED), when this is better for patients. The introduction of electronic health records (EHR) in ambulance services is encouraged by national policy across the United Kingdom (UK) but roll-out has been variable and complex. Electronic Records in Ambulances (ERA) is a two-year study which aims to investigate and describe the opportunities and challenges of implementing EHR and associated technology in ambulances to support a safe and effective shift to out of hospital care, including the implications for workforce in terms of training, role and clinical decision-making skills. METHODS: Our study includes a scoping review of relevant issues and a baseline assessment of progress in all UK ambulance services in implementing EHR. These will inform four in-depth case studies of services at different stages of implementation, assessing current usage, and examining context. RESULTS: The scoping review identified themes including: there are many perceived potential benefits of EHR, such as improved safety and remote diagnostics, but as yet little evidence of them; technical challenges to implementation may inhibit uptake and lead to increased workload in the short term; staff implementing EHR may do so selectively or devise workarounds; and EHR may be perceived as a tool of staff surveillance. CONCLUSIONS: Our scoping review identified some complex issues around the implementation of EHR and the relevant challenges, opportunities and workforce implications. These will help to inform our fieldwork and subsequent data analysis in the case study sites, to begin early in 2017. Lessons learned from the experience of implementing EHR so far should inform future development of information technology in ambulance services, and help service providers to understand how best to maximize the opportunities offered by EHR to redesign care.